The Relationship between Mother's Knowledge About the Occurrence of Oral Trush and the Immune System of Old Babies 0-6 Months - Qoniah, Wardah (Cattleya Darmaya Fortuna, 2022)
Oral thrush is a common condition in the oral cavity that can affect individuals of all ages, including infants and toddlers. This research focuses on studying the relationship between maternal knowledge about oral thrush and the immune system of infants aged 0-6 months. Conducted in 2023 in Pidoli Lombang Village, Panyabungan District, Mandailing Natal Regency, this study employs a descriptive approach within a case study framework. A total of 41 participants were selected using a total sampling technique. Data was collected through a questionnaire consisting of 20 statements and analyzed through editing, coding, and tabulating methods. The findings reveal a significant correlation between maternal knowledge about oral thrush and the immune system of infants. The study underscores the importance of health workers in providing comprehensive health services, particularly in oral hygiene education, to enhance public awareness and prevent oral thrush in infants.